2012
DOI: 10.1084/jem.20111174
|View full text |Cite
|
Sign up to set email alerts
|

STAT5 is a potent negative regulator of TFH cell differentiation

Abstract: Interleukin 2, STAT5, and Blimp-1 work together to suppress differentiation of follicular helper T cells in mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

23
477
2
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 438 publications
(503 citation statements)
references
References 52 publications
23
477
2
1
Order By: Relevance
“…Accordingly, signals generated by the IL-2 receptor during early T cell activation can influence the balance between Tfh differentiation and other effector T cell fates [127,128] via signal transducer and activator of transcription (STAT)-5-dependent skewing of the Bcl6/PR domain zinc finger protein 1 (BLIMP1) ratio [129]. Elegant experiments have used MHC class II tetramers to home in on antigen-specific T cells following influenza infection in mice and have shown that IL-2 administration selectively decreases the number of Tfh cells (CXCR5 1 PD1 1 ), but not other effector T cells (CXCR5 -PD1 -) [130].…”
Section: Il-2 Signalling Impairs Tfh Differentiationmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, signals generated by the IL-2 receptor during early T cell activation can influence the balance between Tfh differentiation and other effector T cell fates [127,128] via signal transducer and activator of transcription (STAT)-5-dependent skewing of the Bcl6/PR domain zinc finger protein 1 (BLIMP1) ratio [129]. Elegant experiments have used MHC class II tetramers to home in on antigen-specific T cells following influenza infection in mice and have shown that IL-2 administration selectively decreases the number of Tfh cells (CXCR5 1 PD1 1 ), but not other effector T cells (CXCR5 -PD1 -) [130].…”
Section: Il-2 Signalling Impairs Tfh Differentiationmentioning
confidence: 99%
“…Several studies have implicated persistent antigen presentation in Tfh differentiation [117,143], a notion that might fit with the inability of self-antigens to be cleared in autoimmune settings. Interestingly, Tfh differentiation is subject to regulation by a number of pathways that are linked genetically to autoimmunity, including the CD28/cytotoxic T lymphocyte antigen (CTLA)-4 axis [144][145][146][147][148][149][150], IL-2 [127][128][129][130] and the lymphoid-specific tyrosine phosphatase (LYP) encoded by protein tyrosine phosphatase, non-receptor type 22 (PTPN22) [151]. The link between these loci and disease initiation is complex, but modulation of Tfh differentiation adds an additional consideration to the other known roles of the candidate genes in these locations.…”
Section: Il-2 Signalling Impairs Tfh Differentiationmentioning
confidence: 99%
“…There has been some evidence of competition between Bcl6 and STATs at cis-regulatory elements, including the Prdm1 gene locus (29,30). Prdm1 expression is driven by STAT5 in CD4 T cells (9,31). To determine if Bcl6 acetylation affects STAT competition, STAT3 and STAT5 ChIP assays were performed at Prdm1 BRE.…”
Section: Significancementioning
confidence: 99%
“…In B cells, Blimp1 induces plasma cell differentiation and blocks the GC B-cell differentiation program by repressing Bcl6 (8). This reciprocal antagonism also exists in T cells, as Blimp1 directly inhibits Bcl6 expression and supports differentiation of non-Tfh effector cells (2,(9)(10)(11)(12).…”
mentioning
confidence: 98%
“…Conversely, Tfh cells are CD25 lo and BCL6 is known to be a reciprocal regulator of BLIMP-1 (2). As a result, Tfh cells are directly inhibited by IL-2/STAT5-driven induction of BLIMP-1 expression (14,15). In addition, Tfr cells themselves have been described to express BLIMP-1, but its deletion causes their expansion, suggesting that BLIMP-1 acts to inhibit their formation (10), whereas loss of BCL6 results in increased expression of BLIMP-1 by Treg cells (7).…”
mentioning
confidence: 99%